In Vivo Powering of Pacemaker by Breathing‐Driven Implanted Triboelectric Nanogenerator. (17th July 2014) - Zheng, Qiang; Shi, Bojing; Fan, Fengru; Wang, Xinxin; Yan, Ling; Yuan, Weiwei; Wang, Sihong; Liu, Hong; Li, Zhou; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> The first application of an implanted triboelectric nanogenerator (iTENG) that enables harvesting energy from in vivo mechanical movement in breathing to directly drive a pacemaker is reported. The energy harvested by iTENG from animal breathing is stored in a capacitor and successfully drives a pacemaker prototype to regulate the heart rate of a rat. This research shows a feasible approach to scavenge biomechanical energy, and presents a crucial step forward for lifetime‐implantable self‐powered medical devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>